2010
DOI: 10.1007/s00039-010-0089-0
|View full text |Cite
|
Sign up to set email alerts
|

Prime Chains and Pratt Trees

Abstract: Prime chains are sequences p 1 , . . . , p k of primes for which p j+1 ≡ 1 (mod p j ) for each j. We introduce three new methods for counting long prime chains. The first is used to show that N (is the number of chains with p 1 = p and p k px. The second method is used to show that the number of prime chains ending at p is log p for most p. The third method produces the first nontrivial upper bounds on H(p), the length of the longest chain with p k = p, valid for almost all p. As a consequence, we also settle … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(33 citation statements)
references
References 28 publications
(46 reference statements)
0
33
0
Order By: Relevance
“…Key ingredients in the proof are a very recent bound on counts of prime chains from [14] (see §3 for a definition) and estimates for primes in arithmetic progressions. The possible existence of Siegel zeros (see §2 for a definition) creates a major obstacle for the success of our argument.…”
Section: Introductionmentioning
confidence: 99%
“…Key ingredients in the proof are a very recent bound on counts of prime chains from [14] (see §3 for a definition) and estimates for primes in arithmetic progressions. The possible existence of Siegel zeros (see §2 for a definition) creates a major obstacle for the success of our argument.…”
Section: Introductionmentioning
confidence: 99%
“…This tree structure first appears in work of Pratt [13] and was extensively studied in recent work of Ford et al [5]. Our second theorem is a lower bound for the number of distinct primes in the Pratt tree.…”
Section: Theorem 11 Fix a Positive Integer K Then As X → ∞ We Havementioning
confidence: 90%
“…, p k be a chain of primes such that for 2 ≤ j ≤ k we have p j = 2p j−1 + 1; that is we have Conditonally one can do far better than this. Assuming that P(2)(x) ∼ Aπ(x), which by Hooley's result is true under GRH, Ford et al [160] have shown that…”
Section: )mentioning
confidence: 96%